Automated Deduction in Geometry 8th International Workshop, ADG 2010, Munich, Germany, July 22-24, 2010, Revised Selected Papers - Schreck, Pascal; Narboux, Julien; Richter-Gebert, Jürgen (Springer eBooks., 2011)
aThis book constitutes the thoroughly refereed post-workshop proceedings of the 8th International Workshop on Automated Deduction in Geometry, ADG 2010, held in Munich, Germany in July 2010. The 13 revised full papers presented were carefully selected during two rounds of reviewing and improvement from the lectures given at the workshop. Topics addressed by the papers are incidence geometry using some kind of combinatoric argument; computer algebra; software implementation; as well as logic and proof assistants.